Where the change is: everyday interaction rituals of therapeutic communities - Clarke, Jenelle M. (2015)
This thesis has been concerned with how everyday social interactions facilitate personal change in the lives of therapeutic community (TC) client members. TCs are planned social environments that aim to provide a safe setting whereby troubling relational patterns can be explored through confronting past trauma and dysfunctional interpersonal dynamics. All aspects of community life, particularly everyday social encounters, such as smoking breaks and meal times, are potentially therapeutic. Whilst there are have been numerous studies focusing on treatment effectiveness and clinical outcomes, there have been relatively few studies that explore how interactions during these potentially therapeutic informal periods facilitate personal change. Thus, everyday social encounters are not only underrepresented in the literature in terms of mechanisms of personal change, they remain poorly understood in practice.